2022
DOI: 10.1155/2022/5067544
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin-5 Knockdown Accelerates Pressure Overload-Induced Cardiac Hypertrophy in Mice

Abstract: A recent study showed that peroxiredoxins (Prxs) play an important role in the development of pathological cardiac hypertrophy. However, the involvement of Prx5 in cardiac hypertrophy remains unclear. Therefore, this study is aimed at investigating the role and mechanisms of Prx5 in pathological cardiac hypertrophy and dysfunction. Transverse aortic constriction (TAC) surgery was performed to establish a pressure overload-induced cardiac hypertrophy model. In this study, we found that Prx5 expression was upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Hu C. et al described that Prx5 expression was upregulated in hypertrophic hearts and cardiomyocytes. In addition, Prx5 knockdown accelerated pressure overload-induced cardiac hypertrophy and dysfunction in mice by activating oxidative stress and cardiomyocyte apoptosis [ 31 ]. Kunze A et al reported on decreased Prdx5 levels in severe stroke [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hu C. et al described that Prx5 expression was upregulated in hypertrophic hearts and cardiomyocytes. In addition, Prx5 knockdown accelerated pressure overload-induced cardiac hypertrophy and dysfunction in mice by activating oxidative stress and cardiomyocyte apoptosis [ 31 ]. Kunze A et al reported on decreased Prdx5 levels in severe stroke [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the long-term effect of pre-and post-cardiac overload, hypertrophic cardiomyocytes are more sensitive to oxidative damage caused by ischemia, hypoxia and ROS, and are superimposed on inflammatory factors, high levels of Ca 2+ , NO and other stimulatory factors, resulting in an increase in cytoplasmic density and cell membrane permeability, nuclear pyknosis and fragmentation, and DNA degradation, leading to the occurrence of cardiomyocyte apoptosis (Hu et al, 2022). In this paper, the apoptosis of cardiomyocytes was observed by flow cytometry, and it was found that GXN had a certain inhibitory effect on the apoptosis process in hypertrophic cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…DUSPs regulate the downstream effectors (ERK, JNK and p38) of MAPK signaling pathway through dephosphorylating the upstream MAPK molecules, such as ASK1, TAK1, and MEK [24]. Accumulating data suggest that the over-activated MAPK signaling pathway promotes the pathological progress of myocardial hypertrophy [25]. Thus, DUSPs might control cardiac remodeling induced by the pathological stimulus through negatively regulating MAPK signaling cascades.…”
Section: Discussionmentioning
confidence: 99%